Bridging the gap: telemedicine as a solution for HIV care inequities in rural and vulnerable communities - Chisom Ogochukwu Ezenwaji; Esther Ugo Alum; Okechukwu Paul-Chima Ugwu (International Journal for Equity in Health)
Abstract Background Despite advancements in HIV management, healthcare inequalities continue to exist, especially in rural and populations vulnerable to HIV, where factors such as distance, low income, prejudice, and a shortage of healthcare workers contribute to delayed diagnosis and inadequate care. Objective This commentary explores how telemedicine can close the healthcare disparity gap for HIV patients in rural and vulnerable settings by bringing care closer and decreasing stigma. Methods The study analyzed primary sources, such as articles from PubMed, Science Direct, the Web of Science, and WHO reports from 2020 to 2024, including case studies, to examine the role of telemedicine in global HIV care. It assessed challenges, effectiveness, and infrastructural barriers, as well as policy implications. Results Telemedicine in HIV care for rural and vulnerable groups includes virtual consultation, monitoring, telehealth, digital health education, diagnostic services, telecounselling, telemental health, telepreventive care, and emergency services. It improves treatment involvement, reduces travel, ensures confidentiality, and reduces social disapproval. However, internet inefficiency and infrastructure issues in isolated regions hinder its use. Conclusion Telemedicine effectively addresses HIV care gaps in rural and high-risk populations by increasing service utilization, reducing stigma, and improving patient care quality; however, long-term sustainability requires infrastructure improvements and internet connectivity issues.